Molybdenum and Cadmium Co-induce Mitochondrial Quality Control Disorder via FUNDC1-Mediated Mitophagy in Sheep Kidney - Wu, Yunhui; Yang, Fan; Zhou, Guangbin; Wang, Qi; Xing, Chenghong; Bai, He; Yi, Xin; Xiong, Zhiwei; Yang, Shuqiu; Cao, Huabin (Frontiers in Veterinary Science, 2022)
Molybdenum (Mo), fundamental trace mineral for animals and plants, but undue Mo damages animal health. Cadmium (Cd) is a toxic heavy metal that exists in the environment. Nevertheless, the mechanism of Mo and Cd on mitochondrial quality control are still indistinct. The objective of this research was to explore the effects of mitophagy on mitochondrial quality control via the FUNDC1-mediated by Mo and Cd in sheep kidney. Forty-eight 2-month-old sheep were stochastically divided into four groups, as shown below: control group, Mo [45 mg/kg body weight (BW)] group, Cd (1 mg/kg BW) group and Mo (45 mg/kg BW)+Cd (1 mg/kg BW) group, with 50 days feed technique. The results showed that Mo or/and Cd attract an unbalance of trace minerals and vacuoles and granular degeneration of renal tubular epithelial cells, and increase the number of mitophagosomes and vacuole-mitochondria and LC3 puncta and MDA and H2O2 contents, and decrease ATP content in the kidney. Moreover, Mo or/and Cd treatment could upregulate the mRNA levels of FUNDC1, LC3A, LC3B, PGAM5, DRP1, FIS1 and MFF, and the protein levels of FUNDC1, p-FUNDC1, LC3II/LC3I, DRP1, MFF and FIS1, downregulate the mRNA levels of MFN1, MFN2, OPA1, PGC-1α, SIRT1, SIRT3, FOXO1 and FOXO3, and the protein levels of MFN1, MFN2, OPA1 and PGC-1α. Notably, variations of above-mentioned factors in Mo and Cd group were more obvious than in Mo or Cd groups. Taken together, these results displayed that Mo and Cd co-treatment might induce mitochondrial quality control disorder via FUNDC1-mediated mitophagy in sheep kidney.